A Smart Library of Epoxide Hydrolase Variants and the Top Hits for Synthesis of (S)‐β‐Blocker Precursors1. (19th May 2014) - Kong, Xu‐Dong; Ma, Qian; Zhou, Jiahai; Zeng, Bu‐Bing; Xu, Jian‐He
Abstract Microtuning of the enzyme active pocket has led to a smart library of epoxide hydrolase variants with an expanded substrate spectrum covering a series of typical β‐blocker precursors. Improved activities of 6‐ to 430‐fold were achieved by redesigning the active site at two predicted hot spots. This study represents a breakthrough in protein engineering of epoxide hydrolases and resulted in enhanced activity toward bulky substrates.